PENGARUH MACAM PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum) VARIETAS THAILAND DAN CROCK KUNING - Rizky, Goldy Maura; Maryani, Yekti; Arnanto, Driska (Universitas Sarjanawiyata Tamansiswa, 2025)
The research aims to determine shallot varieties (Thailand and Crok Kuning) and the effect of organic fertilizer on the growth and yield of shallots (Allium ascalonicum) in sandy fields. This research was conducted on the sandy land of Depok Beach, Parangtritis Village, Kretek District, Bantul Regency, Yogyakarta Special Region Province. This research was conducted for two months starting 02 October 2023-02 December 2023. This research was structured in a factorial Randomized Complete Group Series (RAKL). The first factor is the shallot varieties including the Thai and Yellow Crok varieties. The second factor for shallot varieties includes organic fertilizer sources consisting of goat manure, leaf compost and cow manure. The variables observed were plant growth variables including plant height, number of plants, number of leaves per cluster, fresh and dry weight of onion plants while yield variables included number of bulbs, bulb diameter, bulb weight per cluster and per ha. Analysis of observed variables uses variance at the 5% level, followed by using DMRT at the α = 5% level. There was no interaction between the treatment of providing various sources of organic fertilizer and shallot varieties on all research variables. The treatment of various types of organic fertilizer showed no significant difference to the growth and yield of shallot plants. The treatment of various types of organic fertilizer showed no significant difference to the growth and yield of shallot plants. The Thai variety of shallots provides higher growth and yield compared to the Crok Kuning variety of shallots.